1993
DOI: 10.1002/bjs.1800801228
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic necrosis: Assessment of outcome related to quality of life and cost of management

Abstract: Ten patients with necrotizing pancreatitis admitted consecutively between August 1990 and August 1991 were studied. They comprised eight men and two women of median age 63 (range 29-73) years. One patient died. The median length of hospital stay was 74 (range 40-150) days. The median number of operations and endoscopic procedures performed per patient was 4 (range 2-7). Investigations performed included multiple bacteriological, radiological, haematological and biochemical tests. The mean cost of management wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0
4

Year Published

1993
1993
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 22 publications
4
47
0
4
Order By: Relevance
“…Consequently, the mean length of stay in hospital is longer and has been reported to be as high as 74 days. 30 The financial burden on institutions is substantial. The cost of treating a patient in intensive care has been calculated to be £1500 per day.…”
Section: Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the mean length of stay in hospital is longer and has been reported to be as high as 74 days. 30 The financial burden on institutions is substantial. The cost of treating a patient in intensive care has been calculated to be £1500 per day.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…The mean cost has been estimated at £18 441. 30 When including quality of life measurements, the total cost of caring for such cases has been calculated to be £2157 per quality-adjusted year of life, with a mean of 8.6 years gained. The long-term outcome for the majority of patients who undergo treatment is good.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…All these studies regard patients operated on for acute illness and, in the majority of them, the patient's reported outcomes were evaluated only after a long time interval following discharge [3][4][5][6][7][8]. The questionnaires used in these six studies were: the Medical Outcome Study 36-Item Short-Form Health Survey (SF-36) in four [4,5,7,8], the Rosser disability and distress index in one [3], and the Karnofsky score, the Rankin score and the Sickness Impact Profile in the remaining one [6]. In one study, the patients completed the questionnaire after 1 year [3], whereas, in the other studies, the questionnaires were completed within 3 years after discharge [4][5][6][7][8].…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…The questionnaires used in these six studies were: the Medical Outcome Study 36-Item Short-Form Health Survey (SF-36) in four [4,5,7,8], the Rosser disability and distress index in one [3], and the Karnofsky score, the Rankin score and the Sickness Impact Profile in the remaining one [6]. In one study, the patients completed the questionnaire after 1 year [3], whereas, in the other studies, the questionnaires were completed within 3 years after discharge [4][5][6][7][8]. While the majority of authors have reported a good quality of life for their patients cured of acute pancreatitis [3][4][5][6][7], others have not [8].…”
Section: Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation